2019
DOI: 10.1017/s000711451900182x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and physiological responses of broiler chickens to dietary supplementation with de-oiled soyabean lecithin at different metabolisable energy levels and various fat sources

Abstract: A 42-d study was conducted to investigate the effects of an emulsifier supplementation (de-oiled soyabean lecithin (DSL)) of diets with different levels of metabolisable energy (ME) and various sources of fat on growth performance, nutrient digestibility, blood profile and jejunal morphology of broiler chickens. Diets were arranged factorially (2 × 2 × 2) and consisted of two concentrations of ME (normal and low), two fat sources (soyabean oil (SO) and poultry fat (PF)) and two levels of DSL supplementation (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…These findings also indicate that a higher dietary dose of EB (2 g/kg) was superior to a lower dose (1 g/kg) in terms of nutrient digestibility and AMEn when applied to low-energy diets, whereas the addition of EB to a normal-energy diet would not have an additional beneficial effect on nutrient digestibility. Previously published studies ( Majdolhosseini et al, 2019 ; Haetinger et al, 2021 ; Nemati et al, 2021 ) indicated that emulsion increased the AMEn value and digestibility coefficients of dry matter, energy, and crude fat in various poultry species, which is consistent with the findings of the current study. Siyal et al (2017) also found that exogenous nutritional emulsifiers, such as lysolecithin, may aid in fatty acid digestion, particularly in the presence of poorly digested lipids and high fat intake rates.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These findings also indicate that a higher dietary dose of EB (2 g/kg) was superior to a lower dose (1 g/kg) in terms of nutrient digestibility and AMEn when applied to low-energy diets, whereas the addition of EB to a normal-energy diet would not have an additional beneficial effect on nutrient digestibility. Previously published studies ( Majdolhosseini et al, 2019 ; Haetinger et al, 2021 ; Nemati et al, 2021 ) indicated that emulsion increased the AMEn value and digestibility coefficients of dry matter, energy, and crude fat in various poultry species, which is consistent with the findings of the current study. Siyal et al (2017) also found that exogenous nutritional emulsifiers, such as lysolecithin, may aid in fatty acid digestion, particularly in the presence of poorly digested lipids and high fat intake rates.…”
Section: Discussionsupporting
confidence: 93%
“…Dietary emulsifiers may enhance the emulsification process, including the stabilization and clearance of the lipid droplet surface by bile salts, so that lipase can attach to the interphase ( Siyal et al, 2017 ). The addition of an emulsifier to the diet may also help to improve the adsorption-desorption equilibrium, which is affected by amphiphilic molecules such as fats, phospholipids, and proteins ( Majdolhosseini et al, 2019 ). As a result, the modifications caused by the exogenous emulsifier may increase the nutrient absorption across the enterocyte membrane, resulting in a greater nutrient bioavailability of the feed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations